A president, a church, and trails west competing histories in Independence, Missouri - Taylor, Jon E., 1968- (University of Missouri Press, 2008)
"Examines the efforts of Independence, Missouri, to preserve and balance competing elements of the city's history: as the hometown of President Harry S. Truman; as the site where Joseph Smith established the Reorganized Church of Jesus Christ of Latter Day Saints; and as the historic gathering place for western emigration"--Provided by publisher.